Ag Doped Titanium Dioxide Nanocomposite‐modified Glassy Carbon Electrode as Electrochemical Interface for Catechol Sensing. Issue 3 (14th August 2015) - Ravishankar, T. N.; Suresh Kumar, K.; Teixeira, S. R.; Fernandez, C.; Ramakrishnappa, T.
Abstract: The electrochemical sensing of catechol (CC) on a glassy carbon electrode modified with the ionothermal assisted synthesis of Ag doped TiO2 a nanoparticle has been successfully demonstrated for the first time.Ag doped TiO2 nanoparticles composite modified glassy carbon electrode exhibits higher electrocatalytic activity towards oxidation of catechol than glassy carbon electrode itself. The modified electrode also exhibits high selectivity towards this analyte in the presence of some of the metal ions and some of the biological compounds. Linear ranges and the limit of detections with the above electrode are 1–15 µM and 0.0249 µM respectively. The optimized protocol has been utilized for monitoring the catechol in some of the natural samples like apple juice and green tea and in industrial effluents. Abstract :